Brain‐responsive neurostimulation in patients with medically intractable mesial temporal lobe epilepsy. (11th April 2017) - Geller, Eric B.; Skarpaas, Tara L.; Gross, Robert E.; Goodman, Robert R.; Barkley, Gregory L.; Bazil, Carl W.; Berg, Michael J.; Bergey, Gregory K.; Cash, Sydney S.; Cole, Andrew J.; Duckrow, Robert B.; Edwards, Jonathan C.; et al.
Summary: Objective: Evaluate the seizure‐reduction response and safety of mesial temporal lobe (MTL) brain‐responsive stimulation in adults with medically intractable partial‐onset seizures of mesial temporal lobe origin. Methods: Subjects with mesial temporal lobe epilepsy (MTLE) were identified from prospective clinical trials of a brain‐responsive neurostimulator (RNS System, NeuroPace). The seizure reduction over years 2–6 postimplantation was calculated by assessing the seizure frequency compared to a preimplantation baseline. Safety was assessed based on reported adverse events. Results: There were 111 subjects with MTLE; 72% of subjects had bilateral MTL onsets and 28% had unilateral onsets. Subjects had one to four leads placed; only two leads could be connected to the device. Seventy‐six subjects had depth leads only, 29 had both depth and strip leads, and 6 had only strip leads. The mean follow‐up was 6.1 ± (standard deviation) 2.2 years. The median percent seizure reduction was 70% (last observation carried forward). Twenty‐nine percent of subjects experienced at least one seizure‐free period of 6 months or longer, and 15% experienced at least one seizure‐free period of 1 year or longer. There was no difference in seizure reduction in subjects with and without mesial temporal sclerosis (MTS), bilateral MTL onsets, prior resection, prior intracranial monitoring, and prior vagus nerve stimulation. In addition, seizure reduction was not dependent on the location of depth leads relative to the hippocampus. The most frequent serious device‐related adverse event was soft tissue implant‐site infection (overall rate, including events categorized as device‐related, uncertain, or not device‐related: 0.03 per implant year, which is not greater than with other neurostimulation devices). Significance: Brain‐responsive stimulation represents a safe and effective treatment option for patients with medically intractable epilepsy, including patients with unilateral or bilateral MTLE who are not candidates for temporal lobectomy or who have failed a prior MTL resection.